Pathogenesis of Trypanosoma evansi in buffaloes with high and low grade ration - S Partoutomo (Jurnal Ilmu Ternak dan Veteriner, 1996)
Shortages and low grade of forages during the dry season and hard working during paddy cultivation are thought as phenomena triggering clinical diseases or even outbreaks of surra in Indonesia . An experiment using 12 buffaloes, 12-18 months of ages was conducted to disclose that hypothesis . The experimental animals were divided into 4 Groups of 3 animals (2 females and 1 male), Gr*l and Group2 were fed with high grade ration, while Group3 and Group4 with low grade ration. Group I and Group3 were then infected with Trypanosoma evansi Bakit 102 with the dose rate of 107 trypanosomes/head intravenously . Observations were made for 10 weeks after infection . The results indicated that buffaloes in Group I tended to have higher and persistently longer parasitaemia compared to buffaloes in Group3 (P<0 .05). There were only little bitmore severe clinical signs in buffaloes in Group3 compared to those of Groupl . The mean weight gains of buffaloes in Groups with high grade ration was significantly higher compared to those buffaloes in low grade ration (P<0.01), However, it was only slightly different in the weight gain differences between infected and noninfected buffaloes in each Group of ration (about 100 glhead/day)(P>0.05) . The prepatent period of Groupl was 1 .2 days which was not significantly different to 2 days of Group3 (P>0 .05) . There were no direct effects of low grade ration to the pathogenesis of T. evansi . Low grade ration and T. evansi infection complementary reduced the weight gain, consequently buffaloes with low grade ration infected with T. Evansi showed lower weight gain compared to those of high grade ration infected with T. evansi .   Key words : Trypanosoma evansi, pathogenesis, high grade ration, low grade ration